Pengaruh Konten Dakwah Habib Ja’fafr Husein Al-Hadar Di Media Digital Terhadap Sikap Toleransi Beragama Generasi Muda - nia, firda; Thorif Mumtaz Ali; Wiwik Setiyani (Al-MUNZIR, 2026)
The rapid development of digital media has transformed the way young people access and understand religious information. Social media platforms such as YouTube, Instagram, and TikTok have become important channels for disseminating religious messages, including those promoting tolerance and religious moderation. This study aims to analyze the influence of Habib Ja’far Husein Al-Hadar’s digital da’wah content on the formation of religious tolerance among the younger generation. The research employs a descriptive qualitative approach using non-participant observation of da’wah content published on digital platforms. Data were collected by observing communication styles, tolerance messages, and audience responses related to religious diversity. The findings indicate that Habib Ja’far’s content positively contributes to religious tolerance through three main aspects: a dialogical and youth friendly communication style, the reinforcement of tolerance and moderation values, and the presentation of interfaith dialogue that encourages mutual respect and reduces prejudice. These findings support Social Learning Theory, which explains that attitudes and behaviors can be shaped through observation of positive role models. The study concludes that digital da’wah can serve as an effective medium for promoting religious tolerance and strengthening religious moderation among young people.